Dynamics of Maturity of Muslim People of Probo As The Minority in Christian Surroundings - Ningsih Fadhilah; Uswatun Khasanah (Islamic Studies Journal for Social Transformation, 2017)
Religious maturity is a person's ability to understand, live, and apply the noble values ​​of religion he embraces in everyday life. If religious maturity has existed in a person, then all his deeds and religious behavior are always taken seriously and nurtured on a sense of responsibility rather than on the basis of mimicry and merely follow-up. Therefore in Muslim minority society, religious maturity is very important as a defensive fortress against the efforts of Christianization in the region. The main objective of this research is to increase the maturity of Muslim minorities through the counseling strategy of Islam. So the purpose of this research is to find out the religious maturity of minority Muslim community of Purbo Hamlet before and after being given counseling service of Islamic counseling through religious guidance and to know the effectiveness of the strategy of Islamic counseling guidance through religious activities as media of da'wah towards increasing of religious maturity of Muslim minority of Purbo Hamlet Jolotigo Village. This research is an experiment, using quantitative approach with pre-experimental research type and research model one group pre-test post-test design. Two measurements were conducted on aspects of religious maturity, i.e. pre-test and post-test or before and after the counseling service of Islamic counseling. The subjects of 73 household heads and samples taken were 20 persons. The instrument used is to use a questionnaire covering 5 aspects; differentiation, dynamic character, moral consistency, integral and integral heuristics. Research data are also taken through interviews, observation and documentation. The result of this study concluded that: (1) the maturity of the minority Muslims before treatment had the average score of pre-test 74.6, meaning the religious maturity of the Muslim minority family was "less"; (2) the maturity of minority Muslims after the treatment of the score increased in the post test of 85.4, including the category "fair"; (3) counseling strategy of Islamic counseling through religious coaching has proved effective in increasing the maturity of the minority Moslems, seen in the probability value below 0,05 (0.0005 <0,05).